TEKNIK ESTIMASI UKURAN POPULASI SUATU SPESIES PRIMATA - Imran SL Tobing (VIS VITALIS Jurnal Ilmiah Biologi, 2008)
Population size is very important data on wildlife conservation management. To abundance of the species together habitat quality usually used as basic parameter for the existencies of  wildlife.  To estimates accurate population on primates species is very difficult, this mainly due to the techniques of collecting data.  Total count method is the best to be implemented, however, this possible only in small areas or for non-mobile animal.  For mobile animal like primates or other wild animal in large area, we need to use another method.  This paper will discussed and analyse different method that can be use to measured population size of the primate in the wild.